Health Misperception and Healthcare Utilisation among Older Europeans - Sonja Spitzer; Mujaheed Shaikh (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2020)
Health perception biases can have serious consequences on health. Despite their relevance, the role of such biases in determining healthcare utilisation is severely underexplored. Here we study the relationship between health misperception, doctor visits, and concomitant outof- pocket expenditures for the population 50+ in Europe. We conceptualise health misperception as arising from either overconfidence or underconfidence, where overconfidence is measured as overestimation of health and underconfidence is measured as underestimation of health. Comparing objective performance measures and their self-reported equivalents from the Survey of Health, Ageing and Retirement in Europe, we find that individuals who overestimate their health visit the doctor 14% less often than individuals who correctly assess their health, which is crucial for preventive care such as screenings. Lower healthcare utilisation is accompanied by lower out-of-pocket spending (38% less). In contrast, individuals who underestimate their health visit the doctor more often (28% more) and have higher out-of-pocket spending (17% more). We project that underestimating health of the population 50+ will cost the average European country Intl 71 million in 2020 and Intl 81 million by 2060. Country-specific estimates based on population and demographic projections show that countries such as Germany, Denmark and The Netherlands will experience significantly large costs of such misperception. The results are robust to several sensitivity tests and, more important, to various conceptualisations of the misperception measure.
Keywords: 300; Healthcare utilisation; health perception; overconfidence and underconfidence; doctor visits; out-of-pocket expenditures; SHARE data